Study of the causes and clinical characteristics of ketoacidosis in patients admitted to Tishreen university hospital - سمية الصالح; ربا حمدان (Latakia University Journal -Medical Sciences Series, 2022)
Purpose : Studying the local characteristics of ketoacidosis and comparing it with the medical literature in other societies and developing an educational and treatment plan for physicians dealing with diabetic patients, patients, and their families, which improves the results of managing this acute complication and preventing its occurrence. Method: The study sample included 89 patients with ketoacidosis admitted and treated in The Endocrinology Department of Tishreen University Hospital in Lattakia between 2021 and 2022. Results: Ketoacidosis was the diagnosed symptom of diabetes in 4 patients (4.5%), the distribution of patients by gender (females: males) = (1.4: 1), and the average age of the patients in our study was 41.8 ± 13.8 years with the majority of patients between 40-59 years . The second type of diabetes was the most common in our study by 70.8%, but insulin was the most used treatment to reduce blood sugar in patients by 54%. As for the prevalence of symptoms, it was: abdominal pain 76.4%, followed by vomiting 58.4%, fatigue and general weakness 50.3%, and respiratory distress 29.2%. In the study of the predisposing factors for ketoacidosis, sepsis was the most common cause (57.3%), followed by non-adherence to treatment (15.7%), systemic severity (poor general condition) (9%), and diabetes diagnosed for the first time (6.7%), while the remaining (11.2%) was unknown. Reasons Noting that the urinary tract was the most common site of infection (55%), followed by the respiratory tract (27%) and then the digestive tract (12%). Conclusion: Our study showed the tendency of acidosis to occur in the female category with a slight difference, and more likely among patients with type II diabetes, and it manifested symptoms most commonly abdominal pain and vomiting, and that the most important causes in our region are infection, especially urinary infections.